A paisagem urbana numa abordagem cultural da geografia: percepções e vivências na cidade de Sobral-Ce - Paiva, Márcio Luis Alves (2009)
The city reveals the presence of a variety of landscapes, perceived and experienced in different ways by its inhabitants. Based on this assumption, the geographic research below aims to analyze different forms of representation of the urban landscape. As an area of space research, we provide analysis focused on the city of Sobral, located in the northwest of the State of Ceará. By passing the facts which lead to formation of its Scenery (eighteenth century until the end of the twentieth century), Sobral is thus initially analyzed by a geo-historical perspective, portraying the unique character of its urban formation within the spatial context of inlander. Later we discuss their status as "imagined city", thought by some social groups that nurture the development of his landscapes to support the (re) creation and transmission of images of the city linked to aspects of tradition and modernity at the same time. Methodologically speaking, the work includes the use of an explicit literature on the main topics discussed, as well as by means of visits and field observations and analysis of application and interviews. With regard to treatment with perceptions investigated, the research is effective by a qualitative basis, following directions for a renewed Cultural Geography, conducted a humanistic perspective. Thus, knowledge of these representations makes the recognition of the urban landscape of the city of Sobral as a symbolic field of the first order, influential in the perceptions and experiences of its inhabitants.